Detergent‐Assisted Braking of Peptide Translocation through a Single‐Layer Molybdenum Disulfide Nanopore. Issue 11 (12th February 2020) - Si, Wei; Sun, Qianyi; Chen, Chang; Yu, Meng; Sha, Jingjie; Zhang, Yin; Kan, Yajing; Chen, Yunfei
Abstract: Protein sequencing holds the key to unveiling protein dynamics, which is significant for molecular diagnostics and drug design. Single‐molecule sensing based on 2D nanopores is a versatile technique for realizing low‐cost and high‐throughput protein sequencing targets. However, the remaining challenge is that protein translocates rapidly through nanopores, where few current signals can be gathered for accurate protein sequencing. It is theoretically found that adding nonionic detergents to a solution can slow protein molecules by almost one order when they permeate through a 1.4 nm MoS2 nanopore that is slightly larger than the diameter of the peptide but smaller than the diameter of the protein–detergent complex. This slowdown is due to the strong interaction between the hydrophobic parts of the peptide and detergents. Although detergent molecules are added to the system, ionic current blockade levels can be observed for different residues, indicating that the nonionic detergents are excellent candidates for controlling protein translocation process but do not affect the discrimination of single amino acids. This theoretical work motivates experimental efforts in this area and paves a new way for protein manipulation that brings the nanopore technique closer to satisfying the requirement of high‐precision nanopore protein sequencing. Abstract : All‐atom molecular dynamics simulations are performed to investigate the capability of peptide sequencing by a single‐layer molybdenum disulfide nanopore. As a result of the strong interaction between the hydrophobic parts of the peptide and nonionic detergents, the detergents can control the protein translocation process through nanopores but do not affect the discrimination of single amino acids.